2017
DOI: 10.1021/acs.jpcc.7b01934
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium as a Novel UV Plasmonic Material for Fluorescence Decay Rate Engineering in Free Solution

Abstract: We report modification of the ultraviolet (UV) fluorescence decay rate of p-terphenyl dye molecules by magnesium (Mg) nanoapertures in free solution, in comparison with aluminum (Al). Mg nanoapertures exhibit a lifetime reduction of up to ∼7.2×, which to our knowledge is the largest lifetime reduction of a UV fluorescence dye reported so far in the literature. In comparison, Al nanoapertures exhibit a lifetime reduction of ∼5.3×, exceeding the previously reported value ∼3.5× due to smaller aperture size employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Al nanoapertures have been studied as a tool for the modification of fluorescence decay rate of p-terphenyl dye molecules [44,45]. Wang et al [45] reported a lifetime reduction of ≈7.2×, exceeding the previously reported value ≈3.5× by Jiao et al [44].…”
Section: Aluminummentioning
confidence: 92%
See 2 more Smart Citations
“…Al nanoapertures have been studied as a tool for the modification of fluorescence decay rate of p-terphenyl dye molecules [44,45]. Wang et al [45] reported a lifetime reduction of ≈7.2×, exceeding the previously reported value ≈3.5× by Jiao et al [44].…”
Section: Aluminummentioning
confidence: 92%
“…Al nanoapertures have been studied as a tool for the modification of fluorescence decay rate of p-terphenyl dye molecules [44,45]. Wang et al [45] reported a lifetime reduction of ≈7.2×, exceeding the previously reported value ≈3.5× by Jiao et al [44]. The first fabrication of Al film-over substrate for UV surface-enhanced resonance Raman scattering at the deepest UV wavelength used to date (λ = 229 nm) [46] has been reported.…”
Section: Aluminummentioning
confidence: 97%
See 1 more Smart Citation
“…Achieving the brightest emission rate together with short uorescence lifetimes is important for applications on fast biomolecular dynamics, 4,5 single-photon sources, 14 and also for the newly-developing eld of ultraviolet plasmonics. [57][58][59][60][61][62] Here we rationally explore the use of rectangular-shaped nanoapertures milled in aluminum to enhance the uorescence emission rate of single molecules from the near infrared (excitation 635 nm, detection 655 to 755 nm) down to the deep ultraviolet (excitation 266 nm, detection 310 to 410 nm). We use aluminum layers with optimized deposition parameters, 63,64 as the response for gold lms falls below 600 nm and hence gold lms cannot be used efficiently for dyes with emission from the green to the ultraviolet.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] While numerical simulations of plasmonic resonances in aluminum nanoparticles 31,32 and nanoapertures [33][34][35] predict single emitter fluorescence enhancement, the experiments on UV plasmonics have remained largely focused on dense molecular layers deposited on nanoparticle arrays to enhance Raman scattering, [36][37][38][39] or fluorescence. [40][41][42][43] Metal nanoapertures were shown to reduce the fluorescence lifetime, 44,45 but there has been no report so far quantifying the plasmonic-enhanced UV fluorescence at the single protein level. Several reasons contribute to make this a technical challenge: the need for reproducible well-controlled plasmonic structures, the need for a proper characterization approach to deal with the low brightness and photostability of proteins, and the limited stability of aluminum structures in water environment.…”
mentioning
confidence: 99%